Pengaruh Perbedaan Gelling Agent terhadap Karakteristik Fisik Masker Gel Peel Off Ekstrak Daun Murbei (Morus alba L.) - Rahmiati, Nur; Afra , Fairuz Yaumil; Dharmayati , Evy; Septiani , Dewi Ayu (Journal of Pharmaceutical and Sciences, 2025)
Mulberry leaves extract (Morus alba L.) has an IC50 of 8.35 µg/mL which is classified as a very strong antioxidant so it can be used as an active substance in cosmetic preparations such as Peel Off gel masks. An important component in Peel Off gel preparations is Gelling Agent. The type and concentration of each Gelling Agent can affect the characteristics of the preparation. The purpose of this study was to determine the effect of different Gelling Agents on the physical characteristics of Peel Off gel mask preparations from mulberry leaf extract. Mulberry leaves were extracted using the maceration method with 70% ethanol solvent. Peel Off gel mask preparation is made in 9 formulas, namely formula 1-3 using Gelling Agent gelatin, formula 4-6 using Gelling Agent HPMC, formula 7-9 using Gelling Agent Carbopol 940. Physical characterization of the preparation includes organoleptic, homogeneity, pH, spreadability, adhesive power, viscosity and stability test Cycling Test. The results showed that all formulas had the same organoleptic before and after the stability test, formula 1-3 showed inhomogeneity after the stability test was carried out. The pH of formula 1-6 is in the good pH range (5.62-6.37) while F7-9 has a pH value of 7.04-7.31, the spreadability of the preparation decreased along with the increase in the concentration of Gelling Agent, namely from 17 g.cm/sec to 12 g.cm/sec for a load of 150 g, and the increase in the concentration of Gelling Agent affects the results of adhesive power and viscosity of the preparation. The viscosity values of F1-F3 are 3,666-110,000 mPa.s, F4-F7 with a range of 11,333-49,666 mPa.s, and F7-F9 44,333-162,333 mPa.s. Based on the results of the study, it can be concluded that the difference in Gelling Agent in Peel Off gel mask preparations can affect the physical characteristics of the preparation.